Antioxidant capacity and toxicological evaluation of pterospartum tridentatum flower extracts - Ferreira, Fernanda M. (2012)
Pterospartum tridentatum Willk. (prickled broom) is an autochthonous plant, common in Portuguese territory. The yellow flowers are used in traditional medicine, as a potential cure for all body illnesses, mainly for throat irritation treatment or for diabetes, hypertension and hypercholesterolemia therapy.Despite its traditional use, no toxicological assessment has been performed as we know. A high antioxidant activity of P. tridentatum flower water extract was acessed in good agreement with its ESI-MS spectrum that revealed the presence of several flavonoids, as luteolin-O-(O-acetyl)-glucuronide, luteolin-O- glucuronide or isorhamnetin-O-hexoside. Mitocondrial respiratory rates (state 4, state 3 and FCCP-stimulated respiration) and respiratory indexes (respiratory control and P/O ratios) showed no consistent decrease of respiratory and phosphorylative efficiencies for the concentrations tested (up to 500 μg.mL-1). Cytotoxicity evaluation, using MTT assay, was reliable with the previous results. In conclusion, for the concentration range commonly used P. tridentatum flowers usage can be regarded as harmless and trustworthy.